The Effect of Adjuvant Therapy on Metabolic Syndrome in Schizophrenia Patients at Madani Hospital - Indah Kurnia Utami; Yasinta Rakanita; Patricia Novina Nurak; Niluh Puspita Dewi (Journal of Public Health and Pharmacy)
Background: Schizophrenia is a mental disorder that impacts behavior, emotions, and communication. In recent years, atypical antipsychotics have been increasingly prescribed because they significantly reduce both positive and negative symptoms. However, the long-term effects of atypical can cause metabolic syndrome. Additional therapy is provided to maximize the primary therapy and reduce the side effects.